The effect of sinefungin on the macromolecular biosynthesis of Leishmania species - TZORA (Α. ΤΖΩΡΑ), A.; LAWRENCE, F.; ROBERT-GERO, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of the work presented here was the in vitro study of the action of the antibiotic sinefungin on the macromolecules DNA, RNA and the proteins of different isolates of Leismannia spp. in relation to the resistance or to the sensitivity of the strains examined. The mode of action of sinefungin of the Leishmania strains was detected by incorporating radiolabeled thymidine, uridine and leucine into promastigote forms, to study the synthesis of DNA, RNA and proteins respectively. In the sensitive strain L. tropica a statistically significant reduction of the rate of incorporation of thymidine to the DNA of the parasite, resulted to a 64% inhibition of leishmanial DNA synthesis by sinefungin at a concentration of 2.6 mM, when the time of action of the drug was 24 hours. In the sensitive strain L. tropica the reduction of the rate of incorporation of thymidine was depended on the concentration and the time of action of the drug. No inhibition of leishmanial RNA synthesis was observed. Our research showed that the action of the antibiotic sinefungin to the macromolecular biosynthesis of the protozoan Leishmania is independent of the strain and is strongly related with the expression of the sensitivity and the resistance of the strain. The main target of the antibiotic examined was the DNA of the Leishmania strains sensitive to the drug.